Assessment of Ovarian Reserve in Infertile Patients - Begum, Poly; Shaha, Dipti Rani; Sanjowal, Lipika; Barua, Ripon; Hassan, Md Kamrul (Faridpur Medical College Journal, 2017)
Reduced ovarian reserve is a condition characterized by a reduced competence of the ovary to produce oocyte due to advanced age or congenital, medical, surgical and idiopathic causes. Age is considered to be the principal factor in determining the reduction of ovarian reserve, especially in woman over 40 years of age, but it's well known that a premature reduction of ovarian reserve can also occur in young patients. Management of patients with diminished ovarian reserve is challenging for fertility experts and frequently the only option to conceive is represented by assisted reproduction technologies. Here we review the aetiology, presentation and diagnosis of reduced ovarian reserve both in advanced and in young age and we discuss recent advances in the management of infertility of these women. Faridpur Med. Coll. J. Jul 2016;11(2): 74-80